The effect of personal and epistemological beliefs on performance in a college developmental mathematics class - Steiner, Lorraine A. (Kansas State University, 2007)
This study explored the effects of personal epistemological beliefs about mathematics and beliefs about the ability to do well in mathematics on achievement in a college-level, developmental mathematics class. The influences of gender, age, and ethnicity on these beliefs as they relate to mathematics achievement were also explored. The Mathematics Belief Scales (MBS) was adapted from the Indiana Mathematics Belief Scales and Self-Description Questionnaire III to measure beliefs about the time it takes to solve mathematics problems, the importance of conceptual understanding in mathematics, the procedural emphasis in mathematics, the usefulness of mathematics, and self-concept about mathematics. MBS was administered to 159 participants enrolled in Intermediate Algebra over two semesters at an urban, state-supported mid-western university and two small private mid-western universities. Responses to the surveys and scores on the final exams for the Intermediate Algebra courses were analyzed using descriptive statistics, the Pearson product-moment correlations, analysis of variance techniques, and hierarchical regression analysis. Results indicated that students generally held nonavailing beliefs about mathematics and mathematics self-concept. Students typically believed that mathematical problems should be solved within ten minutes. Students generally did not believe that math problems can be solved with logic and reason instead of learned math rules. Over 40% of the students did not believe that mathematics beyond basic mathematics was useful to everyday life. Students were also generally not confident in their ability to solve mathematics problems. Additionally, men’s self-concept was significantly higher than women’s self-concept. Adult learners’ self-concept was also significantly higher than traditional age students’ self-concept. Hierarchical regression analyses revealed that the importance of understanding mathematical concepts positively influenced final exam scores for men more so than women and self-concept positively influenced final exam scores for women more so than men. These results indicate a need for academic experiences at the college-level that will challenge students’ current belief system and provide an environment that is supportive and conducive to building individual self-confidence.
Keywords: personal epistemology; self-concept; developmental mathematics; Education, Adult and Continuing (0516); Education, Mathematics (0280)